Variation in Weight of the Human Pituitary Gland in Different Age & Sex - Rahman, Mushfika; Ara, Shamim; Akter, Farhana; Afroz, Halima; Sultana, Anjuman Ara; Yousuf, Abul Kalam Mohammad; Akhter, Jesmin (Bangladesh Journal of Anatomy, 2014)
Contrext: The pituitary gland produces several hormones that regulate growth, metabolism and reproduction. Deviations from the normal functions of the gland certainly derange the harmony of life. Therefore, this study is important to identify variation in the weight of human pituitary gland in relation to age and sex. Materials & Methods: A cross-sectional analytical type of study was conducted in the department of Anatomy, Dhaka Medical College, on sixty (40 of male and 20 of female) human pituitary glands were collected from unclaimed dead bodies that were under examination in the morgue of department of Forensic Medicine, Dhaka Medical College, Dhaka. The samples were divided into four groups. i.e. Group-A (20-29 years), Group-B (30-39 years), Group-C (40-49 years) and Group-D (50-59 years). The weight of the gland with the stalk was measured by means of a digital electric balance. Results: In male the mean± SD weight of the pituitary gland was found 355.56 ± 49.78, 261.18 ± 52.31, 244.44 ± 51.26 and 210 ± 18.71 mg in group A, B, C and D respectively. In female the mean± SD weight was 381.11 ± 14.53 mg, 345 ± 19.27 mg and 313.33 ± 11.53 mg in group A, B, and C respectively. Conclusion: The weight of the pituitary gland showed gradual decreasing values with advancing age. The mean ± SD weight of male gland in this study was significantly lower than that of female glands. DOI: http://dx.doi.org/10.3329/bja.v11i1.20505 Bangladesh Journal of Anatomy, January 2013, Vol. 11 No. 1 pp 25-29